Engineering Electromagnetics - Hayt, William H.; Buck, John A.; Akhtar, M. Jaleel (Chennai McGraw Hill Education, 2020)
Fulltext
Keywords: Electromagnetic theory; Energy and potential; Magnetic material; Maxwell Equations